Use of ultra-wideband information transmission system in existing communication systems - Abdugafur Khotamov; Tulkin Sultanov; Abduhafiz Jurakulov (Genius Publishing Group, 2023)
This article shows that ultra-wideband information transmission systems based on Radio-over-Fiber (RoF) technology are a promising and innovative technology that allows increasing the speed of information content transmission and improving the quality of services provided. And further use of the RoF system to solve radio engineering problems will improve the quality and range of wireless communications.
Keywords: Ultra-wideband information transmission; wireless communications